Relationship between job satisfaction and job performance at Al-Ikhsan Sports IOI City Mall Putrajaya / Mohammad Amirul Hakeem and Mohammad Adzly Rajli - Hakeem, Mohammad Amirul; Rajli, Mohammad Adzly (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Job satisfaction and job performance are crucial for organizational success [1]. This study investigates major job satisfaction factors, evaluates job performance levels, and examines their relationship among employees at Al-Ikhsan Sports IOI City Mall, Putrajaya. Understanding this connection can help enhance employee motivation, productivity, and overall workplace efficiency [2]. Findings will provide insights for management to improve job satisfaction and performance. This quantitative, non-experimental study used a survey method to collect data from all employees at Al-Ikhsan Sports IOI City Mall (n = 35, s = 32, with a 20% buffer for non-responses). A structured questionnaire measured job satisfaction across key domains and job performance metrics. Descriptive and inferential statistics, including correlation and regression analysis, were employed to examine the relationship between job satisfaction and performance [3].